An Introduction to Mathematical Analysis for Economic Theory and Econometrics. - Corbae, Dean.; Stinchcombe, Maxwell B.; Zeman, Juraj (Princeton : Princeton University Press, 2011)
Providing an introduction to mathematical analysis as it applies to economic theory and econometrics, this book bridges the gap that has separated the teaching of basic mathematics for economics and the increasingly advanced mathematics demanded in economics research today. Dean Corbae, Maxwell B. Stinchcombe, and Juraj Zeman equip students with the knowledge of real and functional analysis and measure theory they need to read and do research in economic and econometric theory. Unlike other mathematics textbooks for economics, An Introduction to Mathematical Analysis for Economic Theory and Ec.
Cover; Preface; User's Guide; Notation; Chapter 1: Logic; Chapter 2: Set Theory; Chapter 3: The Space of Real Numbers; Chapter 4: The Finite-Dimensional Metric Space of Real Vectors; Chapter 5: Finite-Dimensional Convex Analysis; Chapter 6: Metric Spaces; Chapter 7: Measure Spaces and Probability; Chapter 8: The Lp (O, F, P) and lp Spaces, p ... [1 ...]; Chapter 9: Probabilities on Metric Spaces; Chapter 10: Infinite-Dimensional Convex Analysis; Chapter 11: Expanded Spaces; Index.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Econometrics; Economics, Mathematical; Mathematical analysis; Business; Économétrie.; Analyse mathématique.; Affaires; businesses (business enterprises); BUSINESS & ECONOMICS / Econometrics; Business; Econometrics; Economics, Mathematical; Mathematical analysis; Analysis; Wirtschaftsmathematik; Ökonometrie; Mathematik; Wahrscheinlichkeitsrechnung; Ökonometrie.; Theorie